Concentrador Solar Térmico Fresnel Lineal de San Carlos, Salta : Primeros ensayos de operación y funcionamiento (172 m2) - Dellicompagni, Pablo (2016)
This paper shows the latest advances and measurements achieved in a Linear Fresnel Concentrator (LFC), in 2015 and 2016 periods, which is currently installed in the city of San Carlos. The equipment is able to generate steam. Operation tests of different subsystems and measurements of fundamental parameters such as pressures and temperatures of heat transfer fluid, circulation flow, solar radiation, among others, were made. The methodology used for system startup and measurement parameters are performed analogously to a conventional boiler.